2017
DOI: 10.18805/asd.v37i2.7993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Area, Production and Productivity of Groundnut Crop in Telangana

Abstract: India is the fourth largest oilseed producing country in the world. The present study was carried on based on the secondary data collected from varies websites and directorate of economics and statistics. The results reveled that the compound growth rate of area and production of groundnut in India shows a negative trend while the productivity was positive over the years. In pre bifurcated Andhra Pradesh the annual average production of groundnut during 2011-12 was 1231 thousand tons and the annual average yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The work on the trend with respect to area, production and productivity of peanut was moved by G Shruthi et al [5] on extracting the time series data from directorate of economics and statistics, India of the period 2000-01 to 2013-14. Their results are also based on compound growth rate model and showed that the area and production of peanut in India has a decreasing trend while the productivity was increasing trend over the years.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The work on the trend with respect to area, production and productivity of peanut was moved by G Shruthi et al [5] on extracting the time series data from directorate of economics and statistics, India of the period 2000-01 to 2013-14. Their results are also based on compound growth rate model and showed that the area and production of peanut in India has a decreasing trend while the productivity was increasing trend over the years.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ananthapuramu is the southern-most district of the Rayalaseema region of Andhra Pradesh, which was regarded as the key contributing region to the area and production of the groundnut in the state [7]. The district lies between 13 o 40' and 15 o 15' Northern Latitude and 76 o 50' and 78 o 30' Eastern Longitude.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that, the compound growth rates of area, production and productivity of groundnut over the study period was negative and non-significant. Shruthi et al [7] worked on area, production and productivity of groundnut crop in erstwhile Andhra Pradesh from 2000-01 to 2013-14 and observed that in the state, the area and production of groundnut was high in Rayalaseema region compared to other regions of the state. It was also noticed that, from 2001-02 to 2011-12, the change in the area was recorded as 5.02 per cent, while in case of production the change was -27.01 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…Groundnut is the major oilseed and single largest source of edible oils in India. India is the second largest producer of groundnuts after China (Shruthi et al, 2017). Gujarat is the largest producer contributing 25 per cent of the total production of groundnut followed by Andhra Pradesh, Tamil Nadu and Karnataka (Sameer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%